Novel Spinel Multicomponent High‐Entropy Oxide as Anode for Lithium‐Ion Batteries with Excellent Electrochemical Performance - An, Qingbin; Li, Song; Zhou, Jingjiao; Ji, Shijun; Wen, Zhongsheng; Sun, Juncai (Advanced engineering materials, 2023)
High‐entropy spinel oxides (HESOs) are a promising anode material for lithium‐ion batteries (LIBs) due to their high structural stability and theoretical capacity. However, the development of HESOs is mainly limited to five‐component equimolar systems, and the lithium‐storage mechanism is still controversial. A nonequimolar six‐component oxide, (CoMnZnNiMg) 2 CrO 4 , is synthesized using a solution combustion method. The prepared material is a HESOs, consisting of homogeneous nanoparticles with a mesoporous structure. (CoMnZnNiMg) 2 CrO 4 exhibits high rate performance (371 mAh g −1 at 2000 mA g −1 ) and long cycling stability (608 mAh g −1 after 200 cycles at 200 mA g −1 ). A variety of constituent elements exist uniformly and stably in a spinel phase due to the high‐configuration entropy‐induced phase‐stabilization effect, and the synergistic effect of the various valence elements in the material results in the excellent electrochemical performance. The outstanding electrochemical kinetic properties of the HESOs are mainly attributed to the high‐ionic‐diffusion coefficients and pseudocapacitance contributions. In addition, the HESOs electrodes undergo an amorphous conversion during the initial charge/discharge process. It is shown that the rational design and modulation of the active component is an effective way to obtain high‐performance HESOs for LIBs.